Acetylation of Mitochondrial Proteins in the Heart: The Role of SIRT3 - Parodi-Rullán, Rebecca M.; Chapa-Dubocq, Xavier R.; Javadov, Sabzali (Frontiers in Physiology, 2018)
A growing number of studies have demonstrated the role of post-translational modifications of proteins, particularly acetylation, in human diseases including neurodegenerative and cardiovascular diseases, diabetes, cancer, and in aging. Acetylation of mitochondrial proteins has been shown to be involved in the pathogenesis of cardiac diseases such as myocardial infarction (ischemia-reperfusion) and heart failure. Indeed, over 60% of mitochondrial proteins contain acetylation sites, and most of these proteins are involved in mitochondrial bioenergetics. Mitochondrial non-enzymatic acetylation is enabled by acetyl-coenzyme A abundance and serves as the primary pathway of acetylation in mitochondria. Hence, regulation of enzymatic deacetylation becomes the most important mechanism to control acetylation/deacetylation of mitochondrial proteins. Acetylation/deacetylation of mitochondrial proteins has been regarded as a key regulator of mitochondrial metabolism and function. Proteins are deacetylated by NAD+-dependent deacetylases known as sirtuins (SIRTs). Among seven sirtuin isoforms, only SIRT3, SIRT4, and SIRT5 are localized in the mitochondria. SIRT3 is the main mitochondrial sirtuin which plays a key role in maintaining metabolic and redox balance in the mitochondria under physiological and pathological conditions. SIRT3 regulates the enzymatic activity of proteins involved in fatty acid oxidation, tricarboxylic acid cycle, electron transport chain, and oxidative phosphorylation. Although many enzymes have been identified as targets for SIRT3, cardiac-specific SIRT3 effects and regulations could differ from those in non-cardiac tissues. Therefore, it is important to elucidate the contribution of SIRT3 and mitochondrial protein acetylation/deacetylation in mitochondrial metabolism and cardiac dysfunction. Here, we summarize previous studies and provide a comprehensive analysis of the role of SIRT3 in mitochondria metabolism and bioenergetics under physiological conditions and in cardiac diseases. In addition, the review discusses mitochondrial protein acetylation as a potential target for cardioprotection.